Diseño de un marco en madera para bicicleta de ruta (2019)
The project called “Design of a frame was developed and carried out in wood for road bike initially a diagnosis of the current situation of the designs taking into account the regulations under which each manufacturer must govern at a competitive level. With this information already proceeded to propose wood alternatives thanks to the information found in the laboratories of the Francisco José de Caldas District University and pages Internet with which this project could be carried out to be able to select the most qualified for our goals. The optimum material was selected for the design, taking into account Count the information collected and the desired standards. Then proceed to the basic design development taking into account the selection of wood and thus start the calculation and virtual generation of the frame. Additionally, an analysis of the design is carried out through MEF (method of finite elements) to corroborate the desired results. Finally, the financial evaluation of the project was carried out.